The impact of service quality and Cost on logistics service Outsourcing by vietnamese Manufacturing enterprises - Nguyen, Thi Hương Giang (2020)
The impact of service quality and Cost on logistics service Outsourcing by vietnamese Manufacturing enterprises, Chapter 1: Introduction This chapter provides information on research, including the motivation of research, the research objective and the research scope. Chapter 2: Literature review This chapter will firstly introduce the relevant definitions. Next is a summary of related studies from which the research questions, hypotheses and initial research models will be developed. Chapter 3: Research methodology This chapter discusses the research design, the method used, and the data collection procedure. Chapter 4: Data analysis This chapter describes the analysis of the data collected and interpreted and then verifies the hypothesizes in Chapter 2. Chapter 5: Results and discussions The chapter responds to research questions, reveals the theoretical contribution, the practical implications, and the direction of further research.